2019
DOI: 10.1002/ange.201902872
|View full text |Cite
|
Sign up to set email alerts
|

C−H and C−F Bond Activation Reactions of Fluorinated Propenes at Rhodium: Distinctive Reactivity of the Refrigerant HFO‐1234yf

Abstract: The reaction of [Rh(H)(PEt 3 ) 3 ]( 1)w ith the refrigerant HFO-1234yf (2,3,3,3-tetrafluoropropene) affords an efficient route to obtain [Rh(F)(PEt 3 ) 3 ]( 3)b yC À Fb ond activation. Catalytic hydrodefluorinations were achieved in the presence of the silane HSiPh 3 .Inthe presence of afluorosilane, 3 provides aC ÀHb ond activation followed by a1 ,2-fluorine shift to produce [Rh{(E)-C(CF 3 )=CHF}(PEt 3 ) 3 ]( 4). Similar rearrangements of HFO-1234yf were observed at [Rh(E)-(PEt 3 ) 3 ][E= Bpin (6), C 7 D 7 (8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 84 publications
0
6
0
Order By: Relevance
“…Organometallic transition‐metal (TM) complexes play an important role in chemical research and industry, particularly in homogeneous catalysis, where unique reaction patterns are made possible, especially by the involvement of the d‐orbitals of the TM center [1–3] . Quantum‐chemical studies of the underlying reaction mechanisms complement or inspire experimental work and continuously make important contributions to the field [4–10] . However, electronic‐structure calculations on TM complexes are in many cases complicated by the (near‐)degeneracy of partially filled d‐shells resulting, for mild cases, in appreciable static correlation, which might still be treated with single‐reference methods such as coupled cluster singles doubles with perturbative triples (CCSD(T)), [11] or, for more severe cases, in a distinct multireference character, requiring the use of dedicated multireference methods, such as complete active space self‐consistent field (CASSCF), CASSCF with second‐order perturbation theory (CASPT2) or multireference configuration interaction (MRCI) [12]…”
Section: Introductionmentioning
confidence: 99%
“…Organometallic transition‐metal (TM) complexes play an important role in chemical research and industry, particularly in homogeneous catalysis, where unique reaction patterns are made possible, especially by the involvement of the d‐orbitals of the TM center [1–3] . Quantum‐chemical studies of the underlying reaction mechanisms complement or inspire experimental work and continuously make important contributions to the field [4–10] . However, electronic‐structure calculations on TM complexes are in many cases complicated by the (near‐)degeneracy of partially filled d‐shells resulting, for mild cases, in appreciable static correlation, which might still be treated with single‐reference methods such as coupled cluster singles doubles with perturbative triples (CCSD(T)), [11] or, for more severe cases, in a distinct multireference character, requiring the use of dedicated multireference methods, such as complete active space self‐consistent field (CASSCF), CASSCF with second‐order perturbation theory (CASPT2) or multireference configuration interaction (MRCI) [12]…”
Section: Introductionmentioning
confidence: 99%
“…During the reaction of iridium porphyrins and 1,4-difluorobenzene, the C–F activation product was observed first by TLC analysis. Similarly, Braun et al reported C–H and C–F bond activation reactions of Rh­(H)­(PEt 3 ) 3 and refrigerant HFO-1234yf (2,3,3,3-tetrafluoropropene) . The C–F bond activation product Rh­(F)­(PEt 3 ) 3 was obtained in 5 min, whereas the reaction afforded Rh­{( E )-C­(CF 3 )CHF}­(PEt 3 ) 3 after 19 h, in the presence of a fluorosilane, by an initial C–H activation step, followed by a 1,2-fluorine shift.…”
Section: Introductionmentioning
confidence: 88%
“…reactions of Rh(H)(PEt 3 ) 3 and refrigerant HFO-1234yf (2,3,3,3-tetrafluoropropene). 9 The C−F bond activation product Rh(F)(PEt 3 ) 3 was obtained in 5 min, whereas the reaction afforded Rh{(E)-C(CF 3 )CHF}(PEt 3 ) 3 after 19 h, in the presence of a fluorosilane, by an initial C−H activation step, followed by a 1,2-fluorine shift. Very recently, the Pd(PCy 3 ) 2 -catalyzed selective C−F alumination of fluorobenzenes with {(ArNCMe) 2 CH}Al (Ar = 2,6-di-iso-propylphenyl) was reported by Crimmin et al 10 The possible mechanism involves a stepwise process in which the C−H bond breaks and reforms, directing the catalyst to an adjacent C−F site.…”
Section: ■ Introductionmentioning
confidence: 99%
“…35 [Rh(H)(PEt 3 ) 3 ] (1) reacts with HFO-1234yf to give [Rh(F)(PEt 3 ) 3 ] (5) and 3,3,3-trifluoropropene at room temperature (Scheme 10). 36 When the reaction was performed at low temperature, initial coordination of 2,3,3,3-tetrafluoropropene at the rhodium center was observed and [Rh(H)(η 2 -CH 2 CFCF 3 )(PEt 3 ) 3 ] (28) was identified by NMR spectroscopy. Further activation might proceed via insertion of the fluoroolefin into the rhodium-hydrogen bond followed by -fluoride elimination as proposed for 1,2,3,3,3-pentafluoropropene.…”
Section: Reactivity Of 2333-tetrafluoropropene and (E)-1333-tetmentioning
confidence: 99%
“…With [Rh(H)(PEt 3 ) 3 ] (1) or [Rh{Si(OEt) 3 }(PEt 3 ) 3 ] (4) as catalysts and silanes, HFO-1234yf or HFO-1234ze can be converted into 3,3,3-trifluoropropene and the corresponding fluorosilane by hydrodefluorination of the tetrafluoroolefins (Scheme 13). 36,37 The formation of 3,3,3-trifluoropropene causes competition reactions resulting in a decrease in the selectivity, which is more pronounced in the case of HFO-1234ze due to its lower reactivity. Therefore, not only can hydrodefluorination of tetrafluoropropenes be observed, but also hydrogenation, hydrosilylation or C-F bond activation of 3,3,3-trifluoropene.…”
Section: Account Synlettmentioning
confidence: 99%